"Lands that spit and spew": Aimé Césaire's vegetal poetry. (June 2019) - Galbo, Sebastian Charles
Little critical attention has concentrated on the rich botanical imagery of Aimé Césaire's poetry. Far from serving as the placid, bucolic backdrop of Martinique, Césaire's vegetal world is a space of tremendous and unpredictable flux and change. By performing several close readings of Césaire's flora-centric poems in the context of Édouard Glissant's poetics of Relation, this article articulates a notion of "vegetal writing", a kind of critical mode of composition and reading that produces distinct imaginings of creolization through the aesthetic lens of botanical imagery. In doing so, this article argues that Césaire's vegetal poetry posits a challenge to romanticized pastoral renderings of Antillean landscape and, secondly, dominant readings that place Césaire's work in the literary stronghold of Négritude. Instead, reading Césaire's poems alongside Glissant's notion of Relation, vegetal writing creatively obfuscates the lines dividing root/stem, verticality/horizontality, mobile/immobile, self/other — placing the self in an increasingly complex, creolized world of hybridity, transformation, and human possibility.